2017
DOI: 10.1177/2151458516681141
|View full text |Cite
|
Sign up to set email alerts
|

Can Direct Current Electrotherapy Be Used for Patients With Orthopedic Implants?

Abstract: Introduction:Although electrotherapy appears to have particularly interesting applications in the field of postoperative orthopedic rehabilitation, relatively little scientifically based research has been conducted in the area of electrotherapy with regard to safety involving patients with orthopedic implants.Method:Three electrotherapy forms were tested, such as high-volt stimulation (HVS), transcutaneous electric nerve stimulation (TENS), and galvanic current (GAL), using a model system containing a metal im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…People with prior metal implants should not receive electrical stimulation within the area of the implant due to concern for heating of the underlying implants; however, evidence for excluding these patients is lacking and a recent study demonstrated no adverse events in patients with underlying orthopedic instrumentation receiving electrical stimulation. 34 A theoretical risk also exists for people with unhealed or partially healed fractures, as they could have increased fracture displacement due to muscle contractions induced from the electrical stimulation. However, only one case report of electrical stimulation-induced fracture exists in the literature.…”
Section: Potential Contraindicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…People with prior metal implants should not receive electrical stimulation within the area of the implant due to concern for heating of the underlying implants; however, evidence for excluding these patients is lacking and a recent study demonstrated no adverse events in patients with underlying orthopedic instrumentation receiving electrical stimulation. 34 A theoretical risk also exists for people with unhealed or partially healed fractures, as they could have increased fracture displacement due to muscle contractions induced from the electrical stimulation. However, only one case report of electrical stimulation-induced fracture exists in the literature.…”
Section: Potential Contraindicationsmentioning
confidence: 99%
“…People with automated implantable cardioverter defibrillators or pacemakers may be excluded from FES to ensure the electrical stimulation does not damage and interfere with the proper functioning of these devices. People with prior metal implants should not receive electrical stimulation within the area of the implant due to concern for heating of the underlying implants; however, evidence for excluding these patients is lacking and a recent study demonstrated no adverse events in patients with underlying orthopedic instrumentation receiving electrical stimulation 34. A theoretical risk also exists for people with unhealed or partially healed fractures, as they could have increased fracture displacement due to muscle contractions induced from the electrical stimulation.…”
Section: Potential Contraindicationsmentioning
confidence: 99%
“…The metabolic effects of these techniques are also due to increase of biological enzymatic reactions that can cause accelerated oxygen uptake and healing. [ 16 17 ]…”
Section: Introductionmentioning
confidence: 99%